Reproductive effects of endocrine disrupting chemicals, bisphenol-A and 17β-oestradiol, on Cerastoderma edule from south-west England: field study and laboratory exposure. (11th April 2016) - Lusher, Amy L.; Pope, Nick; Handy, Richard D.
Abstract : Endocrine disruption has rarely been reported in field populations of the edible cockle and the context with the general health of the shellfish is unclear. This study examined the reproductive state of two Cerastoderma edule populations over a 6-month period to assess their reproductive condition, the incidence of intersex and presence of parasitic infection. A further seven native sites from south-west England were examined during the peak reproductive season to identify the presence of intersex within the region. Laboratory exposures of organisms collected from field populations showed a significantly female-biased sex ratio compared with controls when exposed to the endocrine disrupting chemicals, bisphenol-A (nominal concentration: 0.1 µg L −1 ) and 17β-oestradiol (nominal concentration: 0.1 µg L −1 ), but none of the chemical exposures induced intersex. Intersex was revealed in seven out of the nine native populations of C. edule sampled at peak reproductive season. The highest incidence and most severe case of intersex were reported at Lower Anderton on the River Tamer which also had a significantly female-biased sex ratio. Additionally, the dominant trematode family was the Bucephalaidae. Parasitic infection influences the maturity of C. edule by lowering both mean gonad index and condition index. These results suggest that endocrine disrupting chemicals could be contributing factors towards the development of intersex in C. edule .